Interaction between tectonics, plutonism and mineralization of the Duna Pb-Ba ore deposit regarding fluid inclusion study (Central Alborz, Iran) - Sadeghi, Alireza; Asiabar, Saeid Hakimi; Nezafati, Nima; Ganji, Alireza; Mukherjee, Soumyajit (Acta Geologica Polonica, 2023)
This article discusses the impacts of overprinting of tectonic and plutonic events on the mineralization of the Duna Pb-Ba ore deposit, according to geologic settings and fluid inclusion studies. The Duna carbonate-hosted deposit contains a significant amount of Ag (18.9–264.3 ppm ), Cu (77–41600 ppm), Sb (32.7–11000 ppm), Sr (63.5– 15100 ppm), and Fluid inclusions with 7.34–23.65 wt.% NaCl equivalent. The homogenization temperature of about 110–285°C, as well as the paragenesis of the minerals shows a difference compared with other Pb-Zn deposits such as the Irish-type and MVT. The ore mineralization in the Duna mine occurred as stratabound, open space-filling, and along the brecciated fault zones. The concordant (stratabound) type of mineralization, with salinity and homogenization temperature of 18.54 to 23.65 wt.% NaCl equivalent, and 113°C to 165°C respectively, is usually typical of MVT-ore deposits, which in this area evolved during the Early Cimmerian orogeny and was later interrupted by mineralization along younger brecciated fault zones with salinity and homogenization temperature of 7.34 to 23.65 wt.% NaCl equivalent, and 113°C to 285°C respectively. This discordant mineralization, which occurred along the faults, formed by the end of the Late Cretaceous and during the Cenozoic as a result of the intrusion of a plutonic mass, and is comparable to the Irish-type ore deposits.
Keywords: Alborz; Overprinting tectonics; Plutonism; Fluid inclusion; Structural control; Duna type ore deposit; Pb-Ba ore deposit; Carbonate-hosted